2019
DOI: 10.1155/2019/5236851
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds from Water-Ethanol Extracts ofTetrapleura tetrapteraProduced in Cameroon, as Potential Protectors againstIn VivoCCl4-Induced Liver Injuries

Abstract: Background. Liver diseases are a global health problem. Medicinal plants are being increasingly used to manage a wide variety of diseases including liver disorders. The aim of this study was to investigate the antioxidant properties and hepatoprotective activity of polyphenolic extract from the fruits ofTetrapleura tetraptera (T. tetraptera).Results. The extract ofT. tetrapterawas administered at doses of 50 mg/kg and 100 mg/kg for 07per osto rats before the induction of hepatotoxicity with of 2 ml/kg of 1:1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…The results of this study showed that heat-treated T. tetraptera and the formulation contain the highest phenolic content, which correlated with the highest antioxidant potentials. This finding has already been reported by Joel et al (2017), Sokamte et al (2019) and Saague et al (2019). Several studies on spices have been reported in parallel with this finding (Khatun et al, 2006;Raj & Arulmozhi, 2013).…”
Section: Total Polyphenols Total Flavonoids and Biological Activities...supporting
confidence: 79%
See 1 more Smart Citation
“…The results of this study showed that heat-treated T. tetraptera and the formulation contain the highest phenolic content, which correlated with the highest antioxidant potentials. This finding has already been reported by Joel et al (2017), Sokamte et al (2019) and Saague et al (2019). Several studies on spices have been reported in parallel with this finding (Khatun et al, 2006;Raj & Arulmozhi, 2013).…”
Section: Total Polyphenols Total Flavonoids and Biological Activities...supporting
confidence: 79%
“…All of the antioxidant activities are positively and strongly (more than 90%) correlated with TPP and TFL contents, meaning that most of the observed effects are due to phenolic compounds. Previous studies (Saague et al, 2019;Sokamte et al, 2019) drew the same conclusions for the two plant species extracts. The increase in antioxidant activity may also be indicative that the neoformation of new antioxidant compounds after heat treatment is more important than the degradation of antioxidant compounds by heat.…”
Section: Total Polyphenols Total Flavonoids and Biological Activities...supporting
confidence: 56%
“…Avidin‐horseradish peroxidase conjugate was utilized to oxidize 2,2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid), which created a chromogen whose concentration was relative to the convergence of the cytokine being assessed. The estimations were performed at 405 nm wavelength by spectrophotometry …”
Section: Methodsmentioning
confidence: 99%
“…Alkaloids, flavonoids, steroids, triterpenoids, saponins, tannins, glycosides, and phenolic 7 Phyllanthus Fraternus Phenolic and flavonoid content 27 Pavetta Indica LINN Flavonoids and their glycosides, alkaloids, sterols, phenolics, lignins, terpenoids, coumarins,saponins,phenols 28 Mimosa Pudica Flavonoids, glycosides, terpinoids, alkaloids, phenol and tannin 10 Terminalia coriacea β -Sitosterol, Stigmasterol, 1H-Inden-1-one,2,3-dihydro-3,3,5,6,-tetramethyl, nhexadecanoic acid, flavonoids and tannins 3 Bambusa Bambos Flavonoids, steroidal alkaloids, etc 11 Rosa Canina Flavonoids, phenolic acids, tannins, carotenoids 12 Garcinia Pedunculata Flavonoids, saponins, glycosides, steroids, alkaloids and phenols 13 Tetrapleura tetraptera Flavonoid,polyphenols,flavanol 29 Feijoa sellowiana polyphenols 15 ISSN: 2250-1177…”
Section: Cynara Scolymusmentioning
confidence: 99%